1977
DOI: 10.1056/nejm197708112970605
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy for Burned Patients When Survival Is Unprecedented

Abstract: Altered states of consciousness often exclude the seriously burned patient from decision making in his own case. During the first few hours of hospitalization, however, even the most severely burned patient is usually alert and mentally competent. When burns are so severe that survival is unprecedented, we use an aggressive approach to decision making to preserve patient autonomy. While still lucid, and with sufficient information, the patient is asked if he wishes to choose between a full therapeutic regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Much research has been conducted on the manner in which people cope during a particularly stressful event such as severe burn (Hamburg et al, 1953;Imbus and Zawacki, 1977), bereavement (Glock et al, 1974;Vachon et al, 1977), surgery (Cohen and Lazarus, 1973;Janis, 1958), and doctoral examinations (Mechanic, 1962). Recently, attention has been paid to how members of the general population cope with the stressors of everyday life, such * Direct all correspondence to: Kenneth M. Bachrach, School of Public Health, University of California, Los Angeles, CA 90024.…”
mentioning
confidence: 99%
“…Much research has been conducted on the manner in which people cope during a particularly stressful event such as severe burn (Hamburg et al, 1953;Imbus and Zawacki, 1977), bereavement (Glock et al, 1974;Vachon et al, 1977), surgery (Cohen and Lazarus, 1973;Janis, 1958), and doctoral examinations (Mechanic, 1962). Recently, attention has been paid to how members of the general population cope with the stressors of everyday life, such * Direct all correspondence to: Kenneth M. Bachrach, School of Public Health, University of California, Los Angeles, CA 90024.…”
mentioning
confidence: 99%
“…Following this general assumption, many contributors to the futility literature have suggested that patients are in the foremost position to decide on therapeutic goals and to determine whether or not they are worth achieving. [17][18][19][20][21][22] Correspondingly, they are in a prime position to evaluate, interpret and contemplate available medical information and to make evaluative judgements about whether a particular treatment modality is appropriate and worth trying. 10 This is generally accepted as true because only patients know how much risk they are willing to take and can judge particular benefits.…”
Section: Patient Knows Bestmentioning
confidence: 99%
“…Of 24 severely burned patients who were given the opportunity to choose between aggressive or supportive care, 21 chose only pain relief. All 24 died (Imbus and Zawacki 1977).…”
Section: Severely I I I P a Tie N Tsmentioning
confidence: 99%